Nanospanlastics For Transdermal and Topical Drug Delivery: Formulation, Characterization, and Therapeutic Applications: Nanospanlastik untuk Penghantaran Obat Transdermal dan Topikal: Formulasi, Karakterisasi, dan Aplikasi Terapeutik - Fitria Rahmadiani; Esti Hendradi; Tutiek Purwanti (Universitas Tadulako, 2026)
Nanospanlastic is an elastic nanovesicular drug delivery system developed to enhance skin penetration, retention, and therapeutic efficacy in topical and transdermal applications. However, variations in formulation methods, characterization parameters, and evaluation approaches across studies have limited the standardization of its performance. This review was conducted systematically in accordance with the PRISMA guidelines. A comprehensive literature search was performed using international electronic databases, including ScienceDirect, Springer, PubMed, SAGE, and Taylor & Francis online, covering publications from 2015 to 2025. The keywords used were